1998
DOI: 10.3758/bf03199164
|View full text |Cite
|
Sign up to set email alerts
|

Encoding of spatial information in images of an outdoor scene by pigeons and humans

Abstract: Pigeons and adult humans searched for a 2-cm 2 unmarked goal in digitized images of an outdoor scene presented on a touch-screen monitor. In Experiment 1, the scene contained three landmarks near the goal and a visually rich background. Six training images presented the scene from different viewing directions and distances. Subsequent unreinforced tests in which landmark or background cues were removed or shifted revealed that pigeons' search was controlled by both proximal landmarks and background cues, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…They concluded that the ability of these avian species to recognize equivalence between pictures and real objects is severely limited when a behavioral task requires a relatively precise correspondence. Although there is evidence that pigeons transfer discrimination from objects to pictures (e.g., Cabe, 1976;Delius, 1992;Watanabe, 1993) and that pigeons may have the ability to use 2-D cues to perceive three dimensionality (Cook & Katz, 1999;Reid & Spetch, 1998;Spetch, Kelly, & Lechelt, 1998), little is known about avian recognition of 2-D images of complex natural objects. In Experiments 2 and 3, we explored this issue.…”
Section: Resultsmentioning
confidence: 98%
“…They concluded that the ability of these avian species to recognize equivalence between pictures and real objects is severely limited when a behavioral task requires a relatively precise correspondence. Although there is evidence that pigeons transfer discrimination from objects to pictures (e.g., Cabe, 1976;Delius, 1992;Watanabe, 1993) and that pigeons may have the ability to use 2-D cues to perceive three dimensionality (Cook & Katz, 1999;Reid & Spetch, 1998;Spetch, Kelly, & Lechelt, 1998), little is known about avian recognition of 2-D images of complex natural objects. In Experiments 2 and 3, we explored this issue.…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, the superior performance in experiment 2 may be the result of increased salience of flower locations owing to the presence of a vertical dimension in the arrays. Fox squirrels, Sciurus niger, show excellent spatial memory in three dimensions when tested in the field (Jacobs & Shiflett 1999), pigeons, Columba livia, appear to attend to three-dimensional relationships when shown multiple two-dimensional views of a scene (Spetch et al 1998) and rats, Rattus norvegicus, in a three-dimensional maze appear to give priority to goal heights when learning goal locations (Grobéty & Schenk 1992).…”
Section: Discussionmentioning
confidence: 99%
“…This idea continues to be supported by recent research in this field [13,20,33], which encourages its use as inspiration for the development of robot localization algorithms.…”
Section: Looking For Landmarks Based On Visual Saliencymentioning
confidence: 80%